PEMBERIAN PSIKOEDUKASI SEBAGAI STRATEGI PENINGKATAN SELF-DISCLOSURE SISWA SISWI SMA KARTIKA XX-1 MAKASSAR - Siti Aisyah Nuralifah Marimin; Nafizah Aulia Q Jamil; Alfyola DwiYuan Alexander; Ahmad Ridfah (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Adolescence is a period of transition from childhood to adulthood. At partner locations, there are still many teenagers who experience difficulties in expressing themselves both internally and externally which will have an impact on the process of social interaction. In connection with the problems obtained, the implementation team carried out a method of providing psychoeducation, pre-test and post-test about self-disclosure with the theme "Who Am I?". The purpose of the pre-test and post-test is to find out the increase in students' understanding before and after giving psychoeducation. By holding this psychoeducation, it is hoped that Kartika XX-1 Makassar High School students can increase their understanding and implement this understanding in everyday life. There were 84 students who participated in providing psychoeducation. Based on the psychoeducation results that have been given, it was found that there was an increase in understanding for SMA Kartika XX-1 Makassar students about self-disclosure as indicated by the difference between the results of the pre-test and post-test. Thus, psychoeducation about self-disclosure can be an effective method of increasing adolescent understanding, especially students at SMA Kartika XX-1 Makassar in the process of expressing themselves.